Sistem Pemasaran Jasa Freelancer IT (Studi Kasus : AMIK Indonesia) - Jhony Syafwandhinata; Lukman Ahmad (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2019)
In line with the development of e-marketing, a new system emerged in the world of marketing and internet-based business called crowdsourcing. The workings of crowdsourcing sites are almost the same as sales terms where this site allows anyone and from anywhere to offer services and promote services on this site, where each member (member) of these sites is an online freelancer. At present, many promotional sites for freelancers have been provided by several communities and individuals who aim to offer goods and services for freelancers online and each service used is charged by freelancers when work is taken on the site. Based on the observations and experience of the author that many are building projects and digital product marketplaces in Indonesia and the World such as; Projects.co.id, Freelancer.com, Upwork, Guru, Elance, Sribulancer, Sribu. However, members who get services from these sites will be charged by the site owner for their services. This study tries to build a project model and digital product marketplace for students that can be used as a form of marketing student services for service enthusiasts. This model will later build an application that enables the marketing of student services to be complex and foster a spirit of entrepreneurship for students who are creative and innovative. The purpose of this study is to analyze the innovation model of the marketing system for freelancers' services and to build a project and digital product marketplace container as a media for promoting IT services for AMIK Indonesia students. Broadly speaking this research is divided into three stages, namely pre-development data collection, development and implementation, and post-development data collection.